2011
DOI: 10.1038/emboj.2011.471
|View full text |Cite
|
Sign up to set email alerts
|

Redox signalling directly regulates TDP-43 via cysteine oxidation and disulphide cross-linking

Abstract: TDP-43 is the major disease protein in ubiquitin-positive inclusions of amyotrophic lateral sclerosis and frontotemporal lobar degeneration (FTLD) characterized by TDP-43 pathology (FTLD-TDP). Accumulation of insoluble TDP-43 aggregates could impair normal TDP-43 functions and initiate disease progression. Thus, it is critical to define the signalling mechanisms regulating TDP-43 since this could open up new avenues for therapeutic interventions. Here, we have identified a redox-mediated signalling mechanism d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
192
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(216 citation statements)
references
References 44 publications
14
192
1
4
Order By: Relevance
“…It was also shown that the RRM1 was aggregation-prone under physical stresses, such as high pressure or agitation, and served as seeds for further aggregation. Because the high pressure and aggregation allow molecular association in solution, regional increases or condensation of TDP-43 may underlie aberrant assembly of RRM1 domains as well as oxidative stress (30,34). In agreement with this notion, higher concentrations of RRM1 were more susceptible to precipitation after shorter periods of mechanical stress and postincubation (data not shown).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It was also shown that the RRM1 was aggregation-prone under physical stresses, such as high pressure or agitation, and served as seeds for further aggregation. Because the high pressure and aggregation allow molecular association in solution, regional increases or condensation of TDP-43 may underlie aberrant assembly of RRM1 domains as well as oxidative stress (30,34). In agreement with this notion, higher concentrations of RRM1 were more susceptible to precipitation after shorter periods of mechanical stress and postincubation (data not shown).…”
Section: Discussionsupporting
confidence: 75%
“…Because a previous report (30) documented that Cys-173 and Cys-175 are among the targets for oxidation to form oligomers of TDP-43 in ALS, the effect of cysteine substitution of Cys-173 and Cys-175 with Ser (C/S mutants) on the RRM1 oligomerization was investigated. Surprisingly, the single C/S mutants (C173S and C175S) displayed accelerated formation of DTT-sensitive oligomers even without agitation (Fig.…”
Section: Identification Of Core Regions Involved In Rrm1 Misfolding-mentioning
confidence: 99%
“…The C-terminal peptide fragment (residues 287 to 322), and the third (residues 227-233) and fifth (residues 253-259) b-strands in RRM2 are also capable of forming ThT-negative, b-rich fibrils 19,28 . In addition, oxidative stressinduced disulphide bond formation via cysteine residues within and close to RRM2 and RRM1 affects TDP-43 oligomerization 27,45 . Whether the TDP-43 oligomers assemble via these regions is unknown, because the aggregated morphologies between our full-length oligomers and fibrils formed from peptides are distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are rather exposed, they may form disulfide bonds with other TDP-43 domains or with another NTD in a hypothetical dimer. Some studies provide evidence for the oxidized state of Cys residues in the RRM domains of full length TDP-43 contributing to aggregation [28,29]. Here, both Cys are in the reduced state as determined on the basis of their 13 Cb chemical shift.…”
Section: Mass Spectramentioning
confidence: 99%